2009
DOI: 10.2478/v10045-009-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Sheath Brown Rot Disease of Rice Caused by Pseudomonas Fuscovaginae in the Peninsular Malaysia

Abstract: Abstract:Relative to the established and well known rice diseases, sheath brown rot caused by Pseudomonas fuscovaginae can be considered new but getting widespread and serious all over the world. Our research was aimed to monitor and quantify the incidence and importance of the disease in Malaysia. A series of field monitoring and sampling were conducted to quantify the incidence and severity of the disease. Laboratory analysis of the collected diseased plant was done to identify the causal organism. Disease r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In this study, P. fuscovaginae, the causal pathogen of SBR of rice in Malaysia has been successfully isolated, identified and characterized. In general, the symptoms of infected rice plants that we have collected were similar to SBR symptoms as described by Razak et al (2009) and Rott et al (1991) which lower parts of the infected leaf sheath appeared light or dark brown, the leaf sheaths became necrotic and dried, a number of flag leaves changed into light or dark brown as well as the infected panicles of the rice grains turned abnormal and discoloured . According to Cottyn et al (1994), there are two main groups of phytopathogenic pseudomonads; the fluorescent group and the non-fluorescent group.…”
Section: Sample Collection and Morphological Characteristicsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, P. fuscovaginae, the causal pathogen of SBR of rice in Malaysia has been successfully isolated, identified and characterized. In general, the symptoms of infected rice plants that we have collected were similar to SBR symptoms as described by Razak et al (2009) and Rott et al (1991) which lower parts of the infected leaf sheath appeared light or dark brown, the leaf sheaths became necrotic and dried, a number of flag leaves changed into light or dark brown as well as the infected panicles of the rice grains turned abnormal and discoloured . According to Cottyn et al (1994), there are two main groups of phytopathogenic pseudomonads; the fluorescent group and the non-fluorescent group.…”
Section: Sample Collection and Morphological Characteristicsupporting
confidence: 78%
“…The discolored grain and spikelet sterility will directly affect the weight and quality of yield (Cottyn et al, 1996;Vidhyasekaran et al, 1984). To date, Razak et al (2009) reported that the distribution of SBR in major granary in Peninsular Malaysia was almost over a half for most regions. Ever since the establishments of SBR in Malaysia, the characteristics of the causal agent of this country have not yet been described or documented in any report.…”
Section: Introductionmentioning
confidence: 99%
“…Next to necrotic lesions on the sheath, S. oryzae and P. fuscovaginae are known to cause signi cant yield losses (Sakthivel 2001;Razak et al 2009;Panda and Mishra 2019). This study showed that the most virulent, toxin-producing isolates strongly affected seed production.…”
Section: Discussionmentioning
confidence: 86%
“…The Gram-negative bacterium P. fuscovaginae causes sheath brown rot in rice plants. It was rst reported in 1976 in Japan and is able to cause a total yield loss (Tanii et al 1976;Razak et al 2009;Weeraratne et al 2019). Sheath brown rot has been reported in 35 countries (CABI, 2020) and is mostly associated with cold and tropical highlands (Batoko et al 1997;Bigirimana 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium was first identified and reported as a pathogen of rice ( Oryza sativa ) in the temperate region of Japan in 1976 [ 2 ]. It has now been described in several other regions of the world where rice and other gramineae food crops are cultivated including Burundi [ 5 ], Madagascar [ 6 ], Mexico [ 7 ], the Philippines [ 8 ], Nepal [ 9 ], Brazil [ 10 ], China [ 11 ], Iran [ 12 ] and more recently in Malaysia [ 13 ] and Australia [ 14 ]. Pfv causes brown sheath rot disease in rice and also in other gramineae food crops including maize ( Zea mays ), sorghum ( Sorghum bicolour ) and wheat ( Triticum aestivum ) [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%